Literacy acquisition in school in the context of migration and multilingualism - Sürig, Inken,Şimşek, Yazgül,Schroeder, Christoph,Boneß, Anja (John Benjamins Publishing Company, 2016)
Verlagsinfo: This book presents the outcomes of a multi-methodical investigation of the processes of literacy acquisition. The focus is on mono- and bilingual first- and seventh-graders in schools in socially underprivileged areas of two major cities in Turkey and Germany. By means of extensive analyses of lesson videos, linguistic tests, interviews and ethnographic research, social, cultural, linguistic, pedagogic and didactic differences on the international, national, local and individual level are aligned with the momentary problem of exercising a school lesson and acquiring literacy on a daily basis. The results contradict to some degree that cultural and linguistic differences actually make a huge difference in the organisation and process of literacy acquisition. With the interdisciplinary background of the book, it addresses academics concerned with migration sociology, migration linguistics, classroom research, and bilingual education. In a broader perspective, the book contributes to the pedagogically and politically significant question how social and cultural characteristics of specific groups are stereotyped and partly unjustly combined in order to reach symbolic solutions for actual problems.
Enthält Literaturangaben und Register
Keywords: Language acquisition; Multilingualism; Literacy programs; Language awareness in children; Language and culture; Education; Bilingual; Sociolinguistics